Parâmetros ecocardiográficos indicadores de gravidade na doença falciforme: valor do strain bidimensional - Maria Betânia Solis Resende (2018)
Sickle cell disease (SCD) is a multisystem disease caused by a mutation in the globin gene, leading to the formation of abnormal hemoglobin resulting in haemolytic anemia, vaso occlusion phenomena and ischemic tissue damage. Early identification of cardiovascular abnormalities in patients with SCD allows establishing effective therapeutic strategies with direct impact on morbidity and mortality. Two-dimensional speckle-tracking strain echocardiography (STE) has been increasingly used for detection of early myocardial changes in a number of pathophysiological processes of the heart. OBJECTIVES: the study was designed to examine the prognostic value of STE in predicting clinical outcome in patients with SCD and to assess echocardiographic parameters that indicate disease severity. METHODS: A total of 233 SCD adult patients were prospectively enrolled. Patients performed two-dimensional Doppler echocardiography. Measurements of STE were quantified and evaluated. The study endpoint was a composite of the following events during the follow-up: (1) all-cause mortality, (2) three or more acute painful episodes that require hospitalization in one year, (3) acute chest syndrome and (4) hospitalization for disease complication. RESULTS: 165 patients (72.7%) carrying hemoglobin (Hb) SS, 56 patients (24.7%) HbSC and 6 patients (2.6%) with sickle cell-beta zero thalassemia (HbS-β0-thal). The mean age of the patients was 33 ± 11 years (range 18-69 years). During the mean follow-up of 32 months (ranging from 1.2 to 82.6 months), 69 patients (32%) had reached the endpoint, including 8 deaths due to SCD (3.6%). The majority of the patients had preserved systolic function, with LV and LA diameters enlargement. Left atrial volume index and LV indexed mass were increased. No difference was observed in the parameters of diastolic function when we compared the groups with and without adverse events during the follow up. Right ventricle (RV) systolic function was similar in both groups, including RV global longitudinal strain. LV global longitudinal strain ranged from -12.25 to -25.44 (mean -20.26 ± 2.3). Several clinical, laboratory and echocardiographic variables were tested to evaluate a possible association with adverse events. In the multivariate analysis, the maximal velocity of tricuspid regurgitation, LV ejection fraction, LV indexed mass, LA volume index and LV global longitudinal strain were associated with adverse events. CONCLUSION: Higher LV global longitudinal strain was an independent predictor of adverse outcome in patients with SCD, adding incremental prognostic value to the other echocardiographic parameters. Strain assessment has a potential value for clinical risk stratification in SCD patients.